Learning to Write Programs using Think-Pair-Share Programming Strategy: What are the Students’ Perceptions and Experiences? - Owodunni Adewale Saka (Universitas Riau, 2020)
The need to learn programming to solve many complex problems facing humankind necessitated this study. The purpose of the study was to collect information about students’ perceptions and experiences after exposure to the think-pair-share programming strategy. The sample consisted of 12 senior secondary school two students offering computer studies in Ijebu zone, Ogun State, Nigeria purposively selected from the two experimental groups. The data were collected through one-on-one in-depth interviews of the respondents using a Student Interview Guide (SIG). The data analysis was through thematic content analysis procedure. The study found that the respondents perceived the think-pair-share programming strategy helpful to learn programming concepts with or without computers. The study also found that the use of computer was more useful for the acquisition of programming skills than without the use of computers. Moreover, the study found that programming without computers was perceived to improve thinking. Therefore, the study argued that teachers should adopt the use of think-pair-share programming strategy for learning how to write programs notwithstanding the availability of computers due to its ability to aid knowledge retention.